Family Self-Support in Managing Down Syndrome Children: A Qualitative Study - Farzaneh Noroozi; Zohreh Farrar; Tayebeh Gharibi; Roqayeh Gashmard (The Scientific World Journal)
Background and Aim. Down syndrome (DS) is the most common reason for disabilities caused by genetic disorders. Due to the special nature of this disease and the special needs of children with Down syndrome, they are required to receive their families’ support. Therefore, the recognition of their problems and needs and also the alternatives for resolving them and promoting their life quality are very useful. Also, since very limited qualitative studies have been conducted, it seems necessary to design a qualitative study. Method. This qualitative study was conducted by the content analysis method and through purposeful sampling method with the participation of 26 participants including 15 mothers, 6 fathers, 3 sisters, and 2 brothers of DS children in 2022-2023. The data were collected through semi-structured interviews. Findings. Using the content analysis method of Graneheim and Lundman (2004), the main theme was “Family self-supporting in protecting Down syndrome children.” The subthemes were seven including “trying to find information-support resources,” “Giving importance to child’s health,” “religious beliefs of the family,” “child moral education, helping to child’s relative self-support,” “developing familial support,” and “developing child’s social interactions.” Conclusion and Recommendations. The findings of this study showed that family is the main source of fulfilling the needs of children and their life challenges through using efficient self-support methods. This study introduced family self-support methods in terms of DS children in a way that other families can also manage the problems of their children more efficiently. The present study can be used by trustees of DS to support them and their families. Considering the existence of many problems in children with Down syndrome and the involvement of families, it is suggested that policymakers and community health managers provide the basis for receiving services and social support. For example, it is possible to strengthen the screening systems in the country to diagnose the disease on time and take quick action to solve this problem. Also, by increasing the health insurance coverage and fair distribution of the support resources needed by these people, it promoted the quality of life for them and their families. Also, health policymakers in Iran can take action to increase life expectancy and reduce deaths caused by DS by improving the equitable distribution of health resources and services. Also, public policies should enhance supportive intermediation for prevention and life quality promotion and also decrease health challenges. They are also supposed to lessen the costs of health care. Furthermore, to support social organizations, health service providers and researchers should consider the development of intermediations for the health enhancing and life quality promoting of DS children.